Holocene glacial oscillations in the Tyroler Valley (NE Greenland) - Garcia‐Oteyza Ciria, Julia (2023)
Although the spatiotemporal oscillations of the Greenland Ice Sheet (GrIS) during the last millennia have played a prominent role in global environmental changes, its glacial response to the natural variability still needs to be better constrained. Here, we focused on the reconstruction of the glacial behavior and deglaciation process along the Tyroler Valley (74° N, 22° E), within the Northeast Greenland National Park. This NW-SE valley connects with the GrIS via the Pasterze Glacier and divides two ice caps (A.P. Olsen Land and Payer Land), this last one feeding two piedmont glaciers (Copeland and Kløft glaciers). For this study, we combined the interpretation of the spatial pattern of geomorphological features and the chronological framework defined by a new dataset of 15 10Be cosmic-ray exposure (CRE) ages from glacially polished bedrock surfaces and moraine boulders together with one optically stimulated luminescence (OSL) age of a glaciolacustrine deposit. CRE ages indicate that the deglaciation of the lowest parts of the valley and the exposure of the highest slopes took place during the Early Holocene, at ca. 10–8.5 ka (ka = thousand year [BP]). Furthermore, this ice thinning also favored the disconnection of the valley tributary glaciers. Samples from the moraines of the two tributary glaciers indicate that the deglaciation was not continuous, but it was interrupted by at least three phases of glacial advance during the Neoglacial cooling (before ca. 5.9 ka), and the Little Ice Age (LIA, 0.6, and 0.3 ka). The larger piedmont glacier (Copeland Glacier) occupied the valley floor during these major advances, damming the river and allowing the formation of a proglacial glacial lake upvalley, as confirmed by the OSL date of lacustrine sediments that yielded an age of 0.53 ± 0.06 ka. In short, our study provides new evidence of the relative stability of GrIS and the regional ice caps in the area, in which glacial fronts have been rather stable since their advances during the Neoglacial and the LIA.